Numercial Analysis Of Steel Depassivation By The Action Of Chloride Ions In Reinforced Concrete Structures - Roberto Pettres; Ahiram Roquitski; Rafael Rocha (Numerical Methods in Civil Engineering)
This paper presents an application of the Boundary Element Method (BEM) in engineering to simulate and numerically analyze the process of accumulation of chloride ions in a reinforced concrete structure. The study begins with a brief review of the origin of reinforced concrete and the phenomenon of depassivation of reinforcement. The geometric and mathematical model considers two types of concrete characteristics, seeking to numerically represent the concrete used in the construction of beams and pillars of buildings and bridges, covered with an external layer and/or surface protection. In the simulations, it was possible to record the concentration of chlorides in the position occupied by a steel rod in the reinforcement, calculating the number of years necessary to cause the steel to depassivate. In addition to concrete, two materials with different diffusivities were used for the coating layer and two values for its thickness, both related to the time required for the start of the reinforcement corrosion process. The results were obtained with a correlation level of 0.99954 for the R2 estimator, presented in the formulation validation section 4.1, allowing to obtain important information about the steel depassivation process with and without the use of surface protection, making it possible to calculate the start time of reinforcement depassivation under different conditions, the details of which are presented below.